Efficacy of Bacillus clausii and Saccharomyces boulardii in Treatment of Acute Rotaviral Diarrhea in Pediatric Patients - Vineeth, Salloju; Saireddy, Shagamreddy; Keerthi, Thallapalli; Mantada, Prasantha Kumari (Indonesian Journal of Clinical Pharmacy, 2017)
Diarrhea disease is considered as major health problem in developing countries. Rotavirus is the most common identifiable viral cause of diarrhea in all children and belongs to Reoviridae family. Rotavirus infection occasionally leads to severe dehydration in infants and children. The objective of the study is to assess the efficacy of Bacillus clausii and Saccharomyces boulardii on the treatment of rotaviral diarrhea, and also to assess its effect on vomiting and fever in pediatric patients. This study conducted at Rainbow Childrenâs Hospital, Hyderabad, India, from January 2016 until June 2016 and adopts prospective observational parallel study design. From 104 patients enrolled, 80 fulfilled inclusion criteria and 24 were excluded from the study. Patients were divided into two groups based on the treatment. Group I patients were treated with Bacillus clausii and Group II patients were treated with Saccharomyces boulardii. Total mean duration of diarrhea was significantly shorter in Group II (S. boulardii) in comparison with Group I (B. clausii). S. boulardii significantly (pâ¤0.005) decreased the duration of diarrhea which is 25.2 hours over B. clausii. Both probiotic preparations were equal in efficacy on treating the vomiting and fever (pâ¥0.005). S. boulardii and B. clausii were well accepted.